The degree of an Internet addiction among school youth - Niedorys, Barbara; Mikos, Monika; Kocka, Katarzyna; Ślusarska, Barbara (Nursing in the 21st Century, 2018)
THE DEGREE OF AN INTERNET ADDICTION AMONG SCHOOL YOUTH Introduction. The development of mass media, including an Internet has a significant impact on the lifestyle of young people. Despite of universal access and countless opportunities offered via Internet, an increasingly common phenomenon observed for several years is the excessive use of networks by young people, which can lead to Internet addiction. Aim. The aim of this study was to determine the degree of the Internet addiction in a group of junior high school students and high school students and selected conditions of this state. Material and methods. The applied research method was a diagnostic survey, and the following tools: the Kimberly Young’s Internet Addiction Test and the authors’ self-designed survey. The study covered 263 junior high school and high school students. The research was carried out from April to June 2018. Results. The Internet addiction was observed in 11% of the surveyed students. The use of social networking sites was the most common reason for using the Internet among surveyed (95%). The health problems associated with the long time of using the network of addicted students were general fatigue (61%) and lack of sleep (61%). Students addicted to the Internet much more often felt lonely (61%), depressed, upset or sad (n = 22, 78.6%) in contrast to other respondents. Conclusions. Demographic variables (such as: sex, type of school, place of residence) have no significant impact on the development of Internet addiction. Psychosocial functioning has an impact on the development of the Internet addiction.